WOMENâS ROLES IN THE MEDIA - Dewi, Ratna Sari (Lentera: Jurnal Ilmiah Kependidikan, 2012)
The purpose of this paper is to investigate the changes of womenâs roles on how women were potrayed in the past and how they are potrayed today, especially in four influential media. Therefore, the question rised in this paper is âWhat are the changes of womenâs roles on how women were potrayed in the past and how they are potrayed today, especially in four influential media?â. This paper shows that there are many proofs showing changes and improvements of womenâs roles on how women were potrayed in the media in the past, and how they are potrayed today, especially in four influential media such as womenâs magazines, television and print media cartoons and fairy tales. When women are depicted in the media, they they are tipically subjected to a greater degree of phisical appearance and more rigid standard of beauty which they are expected to embody. It argued that the central media messages concerning women is that womenâs primary value lies in their physical appearance.